2020
DOI: 10.1021/acs.macromol.0c02297
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of Nanostructure Development from the Molecular Dynamics of Poly(pentamethylene 2,5-furanoate)

Abstract: We report on the molecular origin of poly(pentamethylene 2,5-furanoate) particular physical properties. From the structural point of view we found this polymer can develop crystallinity when stored at room conditions for months. On the other hand, we used broadband dielectric spectroscopy (BDS) measurements, to analyze in very detail the local and segmental molecular dynamics of the material subjected to several thermal treatments. In this way we evidenced that the molecular dynamics are sensitive to thermal h… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 71 publications
2
19
0
Order By: Relevance
“…Figure 6a reports the thermograms referring to the first heating scan, and it is possible to notice that the as received PPeF utilized in this work is fully amorphous, showing a T g at 17.2 C, which is a temperature close to that found in literature for this material. 43 Being amorphous is a characteristic of the polyesters with a C-odd-numbered glycolic subunit, like PPeF, while those with a C-even-numbered glycolic subunit, such as PBF, POF, PDeF, tend to develop a crystalline structure. 44,51,77 Furthermore, PLA exhibits a T g at 54.1 C, a cold crystallization peak at 96.5 C, and an endothermic melting peak at 166.2 C. Interestingly, both the T g and the T m of PLA are unaltered by the addition of PPeF, and this further confirms that PLA and PPeF are immiscible.…”
Section: Mechanical Propertiesmentioning
confidence: 99%
See 4 more Smart Citations
“…Figure 6a reports the thermograms referring to the first heating scan, and it is possible to notice that the as received PPeF utilized in this work is fully amorphous, showing a T g at 17.2 C, which is a temperature close to that found in literature for this material. 43 Being amorphous is a characteristic of the polyesters with a C-odd-numbered glycolic subunit, like PPeF, while those with a C-even-numbered glycolic subunit, such as PBF, POF, PDeF, tend to develop a crystalline structure. 44,51,77 Furthermore, PLA exhibits a T g at 54.1 C, a cold crystallization peak at 96.5 C, and an endothermic melting peak at 166.2 C. Interestingly, both the T g and the T m of PLA are unaltered by the addition of PPeF, and this further confirms that PLA and PPeF are immiscible.…”
Section: Mechanical Propertiesmentioning
confidence: 99%
“…As reported by Papageorgiou et al, 30 also semicrystalline PPeF could be synthesized, depending on the molecular weight and the processing conditions. Martinez‐Tong et al 43 performed a comprehensive study on the thermal properties of PPeF undergoing different thermal histories. From the DSC analysis, they observed that PPeF was amorphous, but if the PPeF sample was kept for 18 months at room temperature, it reported multiple melting phenomena, which is typical of semicrystalline polymers 43 .…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations